2019
DOI: 10.1096/fj.201900395rr
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp miRNA suppresses the stemness of human cancer stem cellsviathe PIN1 pathway

Abstract: A tumor can be regarded as a cell mass with a biologic hierarchy that is orchestrated by cancer stem cells. The specific features of cancer stem cells may result from a series of gene expression regulatory mechanisms. As important regulatory factors of gene expression, microRNAs (miRNAs) have critical roles in the self‐renewal, pluripotency, differentiation, and tumorigenicity of cancer stem cells. However, the effects of animal miRNAs on cancer stem cells have not been investigated extensively. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…It was discussed that such a liposomal nanoplatform-based approach may be exploited in vivo for silencing cyclophilin A expression in glioma cells to overcome their stemness [202]. Another very original approach has been reported by Zhang and Zhang [203], who used microRNA (mja-miR-35) isolated from a shrimp, Marsupenaeus japonicus, to silence the PIN1 gene in human CSCs. As a result of the action of mja-miR-35, PIN silencing was selectively achieved in melanoma CSCs and breast CSCs, which was accompanied by impairment of their spheroid-forming ability and stimulation of their apoptotic death [203].…”
Section: Targeting Peptidyl-prolyl Isomerases and Use Of Fkbpl-derivementioning
confidence: 99%
See 1 more Smart Citation
“…It was discussed that such a liposomal nanoplatform-based approach may be exploited in vivo for silencing cyclophilin A expression in glioma cells to overcome their stemness [202]. Another very original approach has been reported by Zhang and Zhang [203], who used microRNA (mja-miR-35) isolated from a shrimp, Marsupenaeus japonicus, to silence the PIN1 gene in human CSCs. As a result of the action of mja-miR-35, PIN silencing was selectively achieved in melanoma CSCs and breast CSCs, which was accompanied by impairment of their spheroid-forming ability and stimulation of their apoptotic death [203].…”
Section: Targeting Peptidyl-prolyl Isomerases and Use Of Fkbpl-derivementioning
confidence: 99%
“…Another very original approach has been reported by Zhang and Zhang [203], who used microRNA (mja-miR-35) isolated from a shrimp, Marsupenaeus japonicus, to silence the PIN1 gene in human CSCs. As a result of the action of mja-miR-35, PIN silencing was selectively achieved in melanoma CSCs and breast CSCs, which was accompanied by impairment of their spheroid-forming ability and stimulation of their apoptotic death [203]. This implies that microRNAs from aquatic animals may successfully be used to oppose stemness in human malignancies.…”
Section: Targeting Peptidyl-prolyl Isomerases and Use Of Fkbpl-derivementioning
confidence: 99%
“…As well known, miRNAs are considered to regulate gene expression by binding to the 3’UTRs (untranslated regions) of target mRNAs ( 16 ). In a previous study, 8 miRNAs (miR-9, miR-31, miR-124, miR-133, miR-137, miR-200, miR-210 and miR-2008) were found to participate in the sea cucumber immune response under Vibrio splendidus infection ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio splendidus is one of devastating sea cucumber pathogens, its virulence is particularly high in infected sea cucumber, leading to severe mortalities reach 90% within 7 days of infection ( 14 ). As well known, host ncRNAs are considered to be key regulators of pathogen-host interactions ( 15 , 16 ). Deep sequencing revealed that eight miRNAs were differentially expressed between healthy and SUS-diseased sea cucumbers, in which miR-31, a highly conserved miRNA that regulate cell apoptosis by targeting AjCTRP9 in Vibrio splendidus -challenged Apostichopus japonicus ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of shrimp microRNA as a source of tumour‐targeting agents could be a novel approach in drug discovery. A shrimp miRNA called mja‐miR‐35‐3p (also named mja‐miR‐35) has been found to suppress the proliferation of cancer stem cells by inhibiting peptidylprolyl cis/trans isomerase, never in mitosis gene a–interacting 1 (PIN1) 148 . Shrimp miR‐S8 degrades YB‐1 transcript, and shrimp miR‐965 disrupts the myeloid cell leukaemia sequence‐1‐endoplasmic reticulum stress‐X‐box‐binding protein 1 (MCL‐1‐ER stress‐XBP1) feedback loop, both suppress the tumour progression of human melanoma stem cells 149,150 .…”
Section: Future Perspective In Shrimp Mirna Researchmentioning
confidence: 99%